2010
DOI: 10.4238/vol9-1gmr722
|View full text |Cite
|
Sign up to set email alerts
|

Case Report Benefits of kinesiotherapy and aquatic rehabilitation on sickle cell anemia. A case report

Abstract: ABSTRACT. The process of hemoglobin polymerization and the consequent sickling of red blood cells that occurs in patients with sickle cell disease shortens the half-life of red blood cells. It causes vaso-occlusive complications, as well as pain and pulmonary and cardiovascular dysfunction. We evaluated an aquatic rehabilitation program used for patients with sickle cell anemia and examined the possible benefits that exercise in warm water has for the circulatory system, for relieving pain, and for increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
1
17
0
2
Order By: Relevance
“…Aquatic rehabilitation: Aquatic rehabilitation program found statistically significant reduction in pain [62][63][64]. It is beneficial in the management of patients with musculoskeletal problems, neuropathic and pain problems.…”
Section: Vibration Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic rehabilitation: Aquatic rehabilitation program found statistically significant reduction in pain [62][63][64]. It is beneficial in the management of patients with musculoskeletal problems, neuropathic and pain problems.…”
Section: Vibration Therapymentioning
confidence: 99%
“…Long-term HU is currently the accepted treatment for frequent and severe pain. HU is a potentially leukemogenic and carcinogenic agent [68]. These increases total and fetal hemoglobin in SCD.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…For the subset of skills training therapies that involved physical contact, massage (27,28,31), acupuncture (29,30), healing touch (32), and aquatic rehabilitation (33) were tested. The three massage studies found statistically significant reductions in sensory pain scores, in addition to reduction in opioid use and number of hospitalizations (28).…”
Section: Resultsmentioning
confidence: 99%
“…One case report by Tinti et al found a reduction in pain in a 32 year old SCD female following an aquatic rehabilitation program. [34] This mild exercise program incorporated stretching, aerobic exercise, and relaxation administered in two 45 minute sessions per week for 5 weeks. In a separate clinical study, oxidative stress markers in SCD patients following mild to moderate exercise did not differ from healthy controls.…”
Section: Current Clinical Treatment Of Scd-associated Painmentioning
confidence: 99%